2016
DOI: 10.1021/acs.jnatprod.6b00754
|View full text |Cite
|
Sign up to set email alerts
|

Skeleton Reassignment of Type C Polycyclic Polyprenylated Acylphloroglucinols

Abstract: The previous assignment of the type C skeleton of polycyclic polyprenylated acylphloroglucinols (PPAPs) was controversial and proved to be incorrect in this study. The structures of the type C PPAPs (3-6) were revised to corresponding type A structures (3a-6a) via C NMR spectroscopic analysis and a quantum computational chemistry method. Therefore, only types A and B PPAPs are likely present in plants of the family Clusiaceae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 41 publications
1
25
0
4
Order By: Relevance
“…The same rationale was used to revise co-isolated PPAPs to 25b–26b . 68 It is worth noting that while the 3D structures for 24a and 24b provided in the supplemental information of the revision were correct, the structures of 24a and 24b portrayed in the main manuscript were depicted incorrectly with an α -H at R 3 rather than a β -H. 68 The structures included in the current review are based on the correctly portrayed 3D structures.…”
Section: Structural Revision Based On Computational Prediction Of Nmentioning
confidence: 91%
See 1 more Smart Citation
“…The same rationale was used to revise co-isolated PPAPs to 25b–26b . 68 It is worth noting that while the 3D structures for 24a and 24b provided in the supplemental information of the revision were correct, the structures of 24a and 24b portrayed in the main manuscript were depicted incorrectly with an α -H at R 3 rather than a β -H. 68 The structures included in the current review are based on the correctly portrayed 3D structures.…”
Section: Structural Revision Based On Computational Prediction Of Nmentioning
confidence: 91%
“…In a recent examination of Hypericum cohaerens , the structures of 24–26 were revisited. 68 Three-dimensional models of both type C ( 24a ) and type A ( 24b ) were subjected to a molecular mechanic conformational search followed by DFT geometrical optimization, frequencies and thermochemical computation, and δ C prediction, all at the mPW1PW91/6-31G(d,p) level of theory. The predicted spectroscopic data for 24b were in closer agreement with experimental values, especially for positions 1 and 6, which were the most impacted by the acyl group.…”
Section: Structural Revision Based On Computational Prediction Of Nmentioning
confidence: 99%
“…As shown in Figure 3 , the experimental ECD spectrum of 1 showed good agreement with the calculated ECD curves of 8 S ,9 R ,11 R - 1 and 8 R ,9 R ,11 R - 1 . Then, 13 C NMR calculations [ 29 , 30 , 31 ] were conducted for the two model molecules of 8 S ,9 R ,11 R - 1 and 8 R ,9 R ,11 R - 1 . The results ( Table S5 ) indicated that the experimental 13 C NMR data of 1 are very close to those of the model molecule of 8 S ,9 R ,11 R - 1 with a DP4 + probability score of 100%.…”
Section: Resultsmentioning
confidence: 99%
“…It was noted that the ketonic carbonyl at C-14 of 10 resonated at 180.9 ppm, which is unusual. In order to confirm this possibility, we conducted a computational calculation of its 13 C chemical shifts [18,19,20]. The calculated 13 C NMR data (Table S7) of 10 were in good agreement with its experimental values, with the corrected mean absolute error (CMAE) of 0.28 ppm and the correlation coefficient ( R 2 ) of 0.9982 (Figure 8) and the calculated 13 C chemical shift for C-14 was 184.1 ppm, which was close to the experimental value of 180.9 ppm.…”
Section: Resultsmentioning
confidence: 99%